Recognition of Political Education in Primary Schools - Yayuk Hidayah; Yulia Ngatminiati; Dianasari Dianasari (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2020)
The purpose of this research is to know the efforts of political education in elementary schools. The research methodology used descriptive qualitative research objects were grade V students of SD Negeri Beraja Asri, Way Jepara, East Lampung in Academic Year 2019/2020. Data collection techniques in this study using observation, interviews, and documentation. Data analysis using Miles and Huberman is data reduction, data presentation of conclusions. The results showed that political education in elementary schools could be done in various ways, namely through elementary school PPKn lessons, characterizations, and extracurricular activities. The conclusion in this study is political education in SD Beraraja Asri Way Jepara is integrated into primary PPKn subjects and extracurricular activities.